Social contagion of autonomous motivation among professional educators : as a resource of leadership in schools - Yada, Takumi (2016)
Enhancement of motivation among members in educational organizations is a crucial aspect for leaders to make the organizations more effective. However, when leadership is considered as a process, which makes leadership accessible to every member in an educational organization, the previous studies are still based on the thought that leaders determine leadership styles that motivate fol-lowers. While distributed leadership suggest some implications, it is still un-clear how each member takes on autonomous motivation and it is distributed. Social contagion is the concept that the motivation of the model person spreads to the perceiver. The purpose of this study is to reveal social contagion of autonomous motivation among professional educators including educational leaders and teachers. A sample of 359 Japanese primary and secondary professional educators filled in a questionnaire comprising the adapted editions of the Subscales As-sessing Four Types of Motivation for Teaching (SAFTMT) scale (Roth, Assor, Kanat-Maymon & Kaplan, 2007) and the Perceived Social Power Scale (PSPS) (Imai, 1993). The results indicate that autonomous motivation of professional educators spreads from one to another through social power which consists of attractive, reference, and expert power. In addition, the model persons of the professional educators who have autonomous motivation were mostly the other teachers, not educational leaders such as principals or vice-principals. The current study concludes that educational leaders should pay attention to how their teachers are autonomously motivated and make the most of it.